IDENTIFIKASI KONDISI DAN UPAYA PENINGKATAN BIDANG SUMBER DAYA MANUSIA APARATURUNTUK REFORMASI BIROKRASI DI KOTA SEMARANG - Santoso, R. Slamet (JURNAL ILMU SOSIAL, 2015)
This study aims to determine the conditions, problems and solutions of the implementation of the reform ofthe bureaucracy, especially the changes that occurred in the area of human resources personnel in theGovernment of Semarang City.Based on the survey results revealed that the implementation of bureaucratic reform in this area, are stillnot optimal, thus requiring appropriate treatment measures. The main problem associated with this aspect of thepolicy commitments that have an impact on a wide enough field level implementation .The proposed solution is the start of repair commitments to improvements in front line implementation, forexample the implementation of the planning needs of employees, selection and promotion, education and training,to personnel management information system.